Factors on Mobile Application User Satisfaction in the Largest Indonesian Internet Service Provider (ISP) - Yashella Tirana; Sfenrianto Sfenrianto (CommIT (Communication and Information Technology) Journal, 2023)
Many users complain about using the largest mobile Internet Service Provider (ISP) application in Indonesia, MyIndihome, such as difficulties in verifying, logging in, and changing cell phone numbers and emails. With these complaints, the satisfaction of the MyIndihome application users decreases. The research aims to determine the effect of information quality, system quality, service quality, ease of use, usefulness, and chatbot effectiveness on user satisfaction with MyIndihome. Chatbot effectiveness is a novelty of the research because it has not been studied in previous research. The research applies a quantitative approach. Then the sampling technique used is probability sampling, and the method is simple random sampling with 417 respondents. Data collection techniques are carried out by distributing online questionnaires, and the data are statistically processed with SmartPLS and analyzed by Structural Equation Model (SEM). After carrying out several stages of testing from validity tests, reliability tests, and structural models, the results show that information quality, system quality, ease of use, usability, and chatbot effectiveness have a significant effect on user satisfaction. However, the service quality has no effect. These results can help companies to increase user satisfaction with the MyIndihome application. They can increase the variables that influence user satisfaction with the MyIndihome application.